KBG syndrome: An Australian experience. Issue 7 (27th April 2017) - Murray, Natalia; Burgess, Bronwyn; Hay, Robin; Colley, Alison; Rajagopalan, Sulekha; McGaughran, Julie; Patel, Chirag; Enriquez, Annabelle; Goodwin, Linda; Stark, Zornitza; Tan, Tiong; Wilson, Meredith; et al.
Abstract : In 2011, heterozygous mutations in the ANKRD11 gene were identified in patients with KBG syndrome. Since then, 100 cases have been described with the expansion of the clinical phenotype. Here we present 18 KBG affected individuals from 13 unrelated families, 16 with pathogenic mutations in the ANKRD11 gene. Consistent features included intellectual disability, macrodontia, and the characteristic broad forehead with hypertelorism, and a prominent nasal bridge. Common features included hand anomalies, cryptorchidism, and a large number of palate abnormalities. Distinctive findings in this series included malrotation of the abdominal viscera, bilateral inguinal herniae in two patients, basal ganglia calcification and the finding of osteopenia in three patients. Nine novel heterozygous variants were found and the genotype‐phenotype correlation was explored. This report highlights the need for thorough examination and investigation of the dental and skeletal systems. The results confirm the specificity of ANKRD11 mutations in KBG and further evidence for this transcription repressor in neural, cardiac, and skeletal development. The description of further cases of KBG syndrome is needed to further delineate this condition, in particular the specific neurological and behavioral phenotype.